Pengembangan Kecakapan Literasi melalui Pembelajaran yang Menyenangkan bagi Guru SD Negeri Pandanwangi 3 Malang - Shirly Rizki Kusumaningrum; Radeni Sukma Indra Dewi; Mardhatillah Mardhatillah; Riska Pristiani; Muhammad Syahrul Rizal (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Teachers at SDN Pandanwangi 3 Malang rely heavily on textbooks and powerpoint in their learning activities due to limited references to develop other methods that can attract students' interest. Thus, this training aims to improve teachers' literacy competencies and promote interactive and fun learning methods. Various digital children’s literature were exposed to 30 teachers participating in the training which took place at 17 July (offline), 24 July and 31 July (online via zoom), and 7 August (offline). The training method included material presentation and practical coaching. The results of the training indicated high enthusiasm from teachers in enhancing their literacy competencies and developing interactive and fun learning by integrating reading books.